Spontaneous focusing on numerical order and numerical skills of 3-to 4-year-old children - Harju, Heidi; Van Hoof, Jo; Nanu, Cristina E.; Mcmullen, Jake; Hannula-Sormunen, Minna (SPRINGER, 2025)
Recent studies have highlighted the importance of ordinality skills in early numerical development. Here, we investigate individual differences in ordering sets of items and suggest that children might also differ in their tendency to spontaneously recognize and use numerical order in everyday situations. This study investigated the individual differences in 3- to 4-year-old children's tendency to spontaneously focus on numerical order (SFONO), and their association with early numerical skills. One hundred fifty children were presented with three SFONO tasks designed as play-like activities, where numerical order was one aspect that could be focused on. In addition, the children were administered tasks addressing spontaneous focusing on numerosity (SFON), numerical ordering, cardinality recognition, and number sequence production. Our results showed that children had substantial individual differences in all measures, including SFONO tendency. Children's SFONO tendency was associated with their early numerical skills. To further investigate the association between SFONO tendency and numerical ordering skills, a hierarchical regression was conducted for a group of children who could successfully order sets from one to three at a minimum and were regarded as likely having the requisite skills to spontaneously focus on numerical order. The findings reveal that SFONO tendency had a unique contribution to children's numerical ordering skills, even after controlling for age, cardinality recognition, and number sequence production. The results suggest that SFONO tendency potentially plays a relevant role in children's numerical development.